Resolution of conflict in families with adolescent children - Guerrero San Martín, Fabiola (2019)
Conflicts, being a recurring and daily situation, occur as a result of the coexistence and interrelation of people. The resolution of conflicts within families with adolescent children seeks to identify existing conflicts, differentiating various resolution strategies aimed at their members. This article presents a bibliographic, descriptive and theoretical review of studies related to conflicts, their management and their relationship in families with teenage children, based on the Family Systemic Theory, of contributions from several authors and in a significant way the directives of the Harvard methodology for negotiation, presenting guidelines and strategies that effectively and efficiently help to resolve conflicts, seeking to open a door for help and prevention with significant contributions for consideration and application within families, especially where there are teenage children.